Pelatihan Pembuatan Konten Kreatif Materi Dakwah Digital Bagi Penyuluh Agama Kemenag Kebumen - Fadjeri, Akhmad; Fersellia, Fersellia; Lutfiyani, Anisa; Fachri, Fahmi; Muflih, Ghufron Zaida; Hidayat, Taufik; Wahyuningsih, Endang; Anggoro, Tri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This community service activity aims to improve the ability of religious activists to use digital technology as a means of preaching in accordance with the progress of the times. Through in-depth training that focuses on creating religious content in short video format, participants receive practical training on planning, shooting, and editing videos with the CapCut application. From this training, ten videos with religious themes were produced that have been widely distributed through the most popular social media platforms such as TikTok, Facebook, and YouTube. In addition to creating inspiring and informative works, this training also succeeded in increasing participants' understanding of digital audience trends and preferences, especially the younger generation. This activity shows that with a relevant approach and proper guidance, religious instructors can transform into adaptive, professional, and transformative preaching content creators. Thus, the spread of religious messages can be expanded through digital media in a way that is humanistic, inclusive, and in line with the characteristics of the times